2019
DOI: 10.3389/fimmu.2019.01782
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Killing the Silent Killer: NK Cell-Based Immunotherapy for Ovarian Cancer

Abstract: Ovarian cancer (OC) is diagnosed in ~22,000 women in the US each year and kills 14,000 of them. Often, patients are not diagnosed until the later stages of disease, when treatment options are limited, highlighting the urgent need for new and improved therapies for precise cancer control. An individual's immune function and interaction with tumor cells can be prognostic of the response to cancer treatment. Current emerging therapies for OC include immunotherapies, which use antibodies or drive T cell-mediated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 178 publications
0
41
0
4
Order By: Relevance
“…Besides the application of NK cell stimulating cytokines, the treatment of cancer patients with antibodies targeting inhibitory NK cell receptors or agonists of activating NK cell receptors were used to increase the number and functionality of NK cells. Very recently, a review by Nersesian et al demonstrated the success of NK cell-based therapy in patients with ovarian cancer; however, aspects of obesity were not touched (180). In addition, NK cell adoptive transfer therapies for cancer patients using allogenic blood NK cells, stem cell-derived NK cells, or different NK cell lines exhibited promising effects in the treatment of several cancer types, whereas only limited clinical benefits were observed in cancer patients who received an adoptive transfer of autologous NK cells (181)(182)(183).…”
Section: Nk Cell-based Immunotherapies In Cancer Treatmentmentioning
confidence: 99%
“…Besides the application of NK cell stimulating cytokines, the treatment of cancer patients with antibodies targeting inhibitory NK cell receptors or agonists of activating NK cell receptors were used to increase the number and functionality of NK cells. Very recently, a review by Nersesian et al demonstrated the success of NK cell-based therapy in patients with ovarian cancer; however, aspects of obesity were not touched (180). In addition, NK cell adoptive transfer therapies for cancer patients using allogenic blood NK cells, stem cell-derived NK cells, or different NK cell lines exhibited promising effects in the treatment of several cancer types, whereas only limited clinical benefits were observed in cancer patients who received an adoptive transfer of autologous NK cells (181)(182)(183).…”
Section: Nk Cell-based Immunotherapies In Cancer Treatmentmentioning
confidence: 99%
“…chimeric antigen receptors or cytokines), for fit-for-purpose applications in immunotherapy [21]. Despite their advantages NK cell-based clinical trials have yielded heterogeneous results, likely reflecting further obstacles, such as immunosuppression in a tumor microenvironment, that hinder their reactivity [43,44]. Analysis of miRNA transcriptomes from NK cells derived from peripheral blood, cord blood, and uterine decidua reveal significant differences in miRNA profiles, suggesting that miRNA may help to calibrate and tailor NK cell effector functions.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence shown that the presence of TILs may improve clinical outcome of ovarian cancer patients [40] . Immune cell-based immunotherapy [30] including NK Cells [31] and dendritic cells [32] play important roles in the treatment of ovarian cancer. Our results suggested that CLDN6 may be involved in tumor immune evasion, and may represent ideal candidate for immunotherapy in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the in ltration of these immune cells in the tumor microenvironment is related to the tumor immunotherapy response [29] . Immune cell-based immunotherapy [30] including NK Cells [31] and dendritic cells [32] play important roles in the treatment of ovarian cancer. Taken these analyses together, our research showed that CLDN6 and CLDN10 may play important roles in immunotherapy in the future.…”
Section: Relationship Between Claudins Expression and Gene Markers Ofmentioning
confidence: 99%